(untitled) (New York, 2001)
This book combines an up-to-date summary of how best to genetically engineer viruses with an overview of basic virology. This unique combination makes it an invaluable research tool for virologists and molecular biologists seeking to exploit viruses for a range of applications. Written by highly respected authors, the book also provides comparisons to and guidelines for the use of viruses in difference applications.
Keywords: Recombinant viruses,Virus tái tổ hợp